MODERASI BERAGAMA PERSPEKTIF TAFSIR AL-MUNIR - Mubarak, Abdi; Fatihunnada, Fatihunnada; Nisa, Khaerun (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
This study aims to explore the concept of religious moderation and its indicators as formulated by the Ministry of Religious Affairs of the Republic of Indonesia, based on selected verses from the Qur’an and interpreted through the perspective of Tafsir Al-Munir. The research employs a descriptive-analytical method, in which the author gathers relevant Qur’anic verses and analyzes them using Tafsir Al-Munir as the primary source. Additional data are obtained from classical and contemporary tafsir literature, as well as other supporting scholarly works relevant to the topic. This study emphasizes the importance of balance in the lives of Muslims through the concept of wasathiyyah, national commitment, and the principle of tolerance. Violence and radicalism are considered threats to social harmony, while openness to local culture is encouraged as long as it remains in accordance with Islamic law. In conclusion, balance, tolerance, and appreciation of culture and nationalism are key to building a harmonious and religious society. Penelitian ini bertujuan untuk memahami moderasi agama secara umum dan indikator-indikatornya yang dirumuskan oleh Kementerian Agama RI berdasarkan ayat-ayat Al-Qur'an dan tafsir menurut perspektif Tafsir Al-Munir . Dalam penulisan penelitian ini, penulis menggunakan metode deskriptif analitis. Penulis mengumpulkan ayat-ayat Al-Qur'an yang terkait, kemudian menganalisisnya dengan menggunakan kitab Tafsir Al-Munir sebagai sumber utama. Sedangkan data yang diperoleh dalam penelitian ini dirujuk dari kitab-kitab tafsir dan buku-buku lain yang relevan dengan penelitian ini. Penelitian ini menekankan pentingnya keseimbangan dalam kehidupan umat Islam melalui konsep wasathiyyah, komitmen kebangsaan, serta prinsip toleransi. Kekerasan dan radikalisme dianggap sebagai ancaman bagi harmoni sosial, sementara keterbukaan terhadap budaya lokal dianjurkan selama tetap sesuai dengan syariat Islam. Kesimpulannya, keseimbangan, toleransi, dan penghargaan terhadap budaya dan kebangsaan menjadi kunci dalam membangun masyarakat yang harmonis dan religius.